Ectopic ACTH Syndrome Emerging 5 Years after the Diagnosis of Neuroendocrine Tumor. (28th May 2019) - Liu, Minghao; Hamele-Bena, Diane; Ausiello, John; Page-Wilson, Gabrielle
Abstract : Ectopic ACTH syndrome (EAS) arising years after the diagnosis of a neuroendocrine tumor (NET) is exceedingly rare. We describe a case of EAS occurring five years after the diagnosis of a metastatic lung NET in a 61-year-old woman. She presented with severe hypokalemia but was not overtly Cushingoid on exam. Serum cortisol was 61mcg/dL after an overnight 1mg dexamethasone suppression test (<1.8mcg/dL) and urinary free cortisol was 7544 mcg/24h (<45mcg/24h), establishing the diagnosis of Cushing's syndrome. Plasma levels of peptides which have been associated with EAS, Agouti-related peptide (AgRP) and the ACTH precursors POMC (31-kDa) and pro-ACTH (22-kDa), were elevated. Metyrapone was initiated, but hypercortisolism persisted and the patient succumbed to pneumonia shortly after presentation. Retrospective examination of biopsy tissues showed rare ACTH immunoreactivity at the time of initial diagnosis, followed by staining in a greater proportion of cells as the disease progressed, consistent with EAS arising years after the diagnosis of NET. Given the increase in mortality associated with EAS, this unusual case highlights the importance of early detection and raises the possibility that early immunohistochemical stains for ACTH and measurements of ACTH precursors may facilitate the identification of NETs at high risk for EAS.